A NEW APPROACH TO THE TREATMENT OF ANOVULATORY INFERTILITY IN REPRODUCTIVE-AGE WOMEN - Gafurova, E.O.; Sharipova, Sh.O.; Burxonova, S.B.; Solieva, Z.F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Among the various causes of female infertility, follicle dysfunction accounts for 27%. The aim of the study is to assess the effectiveness of the preservative drug clomiphene citrate in stimulating ovulation in women of different reproductive ages who have anovulatory infertility. Materials. The study included women of different reproductive ages with 70 cases of anovulatory infertility, of which the I group consisted of 30 women of early reproductive age and the II group included 20 women of late reproductive age. Women who were of reproductive age but refused to induce ovulation at age 20 made up the control group. All women were advised to take a drug containing clomiphene citrate in order to stimulate ovulation. When diagnosing the process of anovulation in the ovaries in all women, hormonal and ultrasound examinations were carried out. Results. Ovulation has been achieved in 23 (76.7%) women in Group I. In 2 (8.6%) of them, the dose of the ovulatory clomiphene citrate preservative drug is 100 mg. It happened when I increased to 5 (21.7%) while on 150 mg. Pregnancy occurred in 20 (87.0%) of these women. In Group II, ovulation has been achieved in 13 (65.0%) women. In three (23.9%) of them, the dose of the ovulatory clomiphene citrate preservative drug is 100 mg. It occurred when a dose of 150 mg was increased to 2 (15.3%). Pregnancy occurred in 11 (55.0%) of the women in this group. Conclusion. There is ovulatory infertility the use of the preservative drug clomiphene citrate in stimulating ovulation in women of different reproductive ages has proven its effectiveness by causing ovulation to occur in groups of 76.7% and 65.0%, respectively, and causing pregnancy in groups of 87.0% and 55.0% of women, respectively.